The Contribution of Teaching Logic to Ethical Decision Making - Gonda, Dalibor; Emanovsky, Petr (Communications - Scientific letters of the University of Zilina, 2017)
Everyone makes many important decisions in one’s life and these decisions are the result of one’s thinking. However, in many critical situations one cannot find a solution. The paper deals with the importance of teaching logic in mathematics for the human individual to be able to make ethically correct decisions. The mathematical formalism can simplify thinking and thus achieve the proper conclusion. Teaching logic can help humans learn the basic rules of logical reasoning. Mathematics is essentially a universal language of physics and technology but it can also be a language of communication in ethics. The unambiguity of mathematics could be used to solve many controversial ethical issues in the application of new scientific knowledge.